2017
DOI: 10.7566/jpsj.86.113702
|View full text |Cite
|
Sign up to set email alerts
|

Local Nodal Cooper Pairs in Multiorbital Systems

Abstract: We show the occurrence of a new class of superconductivity in multiorbital systems, focusing on nonKramers f 2 states. The Cooper pairs in this class of superconductivity are mainly local pairs with the same symmetry as the local f 2 ground states. When the local ground state is an anisotropic representation, the superconducting gap has nodes on the Fermi surface. This nodal superconductivity is mediated by the strong on-site interorbital attractions arising from the negative-U physics, generalized in multiorb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…For example, the magneto-electric effects in Cr 2 O 3 [83][84][85] and Co 4 Nb 2 O 9 [86][87][88][89][90] are understood by the M quadrupole, magneto-current effect in metallic UNi 4 B by the MT dipole [91][92][93] , valley splitting in the electronic band structure by the MT octupole 94 , nonreciprocal magnon excitations in BiTeBr 95 and α-Cu 2 V 2 O 7 [96][97][98][99][100] by the E and MT dipoles, orbital Edelstein effect in Te by the ET monopole and quadrupole 101,102 , and large anomalous Hall effect, Nernst effect, and Kerr rotation in Mn 3 Sn by the M octupole 38,[103][104][105][106] . Moreover, unconventional superconductivities are also discussed in the language of multipoles [107][108][109][110] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the magneto-electric effects in Cr 2 O 3 [83][84][85] and Co 4 Nb 2 O 9 [86][87][88][89][90] are understood by the M quadrupole, magneto-current effect in metallic UNi 4 B by the MT dipole [91][92][93] , valley splitting in the electronic band structure by the MT octupole 94 , nonreciprocal magnon excitations in BiTeBr 95 and α-Cu 2 V 2 O 7 [96][97][98][99][100] by the E and MT dipoles, orbital Edelstein effect in Te by the ET monopole and quadrupole 101,102 , and large anomalous Hall effect, Nernst effect, and Kerr rotation in Mn 3 Sn by the M octupole 38,[103][104][105][106] . Moreover, unconventional superconductivities are also discussed in the language of multipoles [107][108][109][110] .…”
Section: Introductionmentioning
confidence: 99%
“…To calculate the multipole susceptibility, in this paper, we resort to the RPA on the basis of the perturbation expansion in terms of the Coulomb interactions. In the RPA, the susceptibility is expressed in a compact matrix form as 28)…”
Section: Multipole Susceptibility In the Rpamentioning
confidence: 99%
“…When we consider the local f -electron states on the basis of the j-j coupling scheme, 24) we notice that the Γ 3 ground states are mainly composed of two singlets among Γ 7 and Γ 8 electrons. [25][26][27][28][29][30] Note that the double degeneracy originates from the orbital degrees of freedom in Γ 8 electrons. This is consistent with the fact that Γ 3 is included in the direct products of Γ 7 and Γ 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In two-orbital models, there is an interesting possibility to realize anisotropic superconductivity originating from the orbital anisotropy. 25,26) For example, we obtained d-wave spintriplet superconductivity in a model for e g orbitals on a square lattice. 25) However, it was shown that a two-orbital model is inadequate for describing the multipole degrees of freedom in the Γ 3 CEF state.…”
mentioning
confidence: 99%
“…Notably, this superconducting phase extends far from the SDW phase and does not require particular fluctuations. Even in an unrealistic two-orbital model for the Γ 3 CEF state, E g superconductivity was obtained, 26) indicating that E g superconductivity is relatively stable in Γ 3 systems.…”
mentioning
confidence: 99%